Aplikasi Migrasi Database dan Replikasi Bi-Directional - Michael Yoseph Ricky (ComTech: Computer, Mathematics and Engineering Applications, 2011)
This study aims to analyze and design a migration and replication configurations in an enterprise using several methods such as literary study and direc survey to the company; analysis on hangar systems, process migration and replication as well as existing problems; and a prototype design for migration process implementated with Oracle SQL Developer and replication process implementated with Oracle GoldenGate. The study resluts ini a prototype for migration and replication configuration processes using Oracle's Golden Gate which can produce two sets of identical data for backup and recovery. Also a simple tool is designed to assist active-active replication process as well as active-passive one. The migration process from MySQL database to Oracle database using Oracle GoldenGate can not be done because GoldenGate Oracle has bugs related to the binary log, so database migration is done using Oracle SQL Developer. However, bi-directional replication between Oracle database using Oracle GoldenGate can ensure data availability and reduce the workload of primary database.